Lean construction como estratégia para melhorias em canteiros de obras: uma revisão sistemática na literatura nacional - Camera, Elaine [UNESP] (2015)
The use of the principles of Lean Construction as a strategy to improvements in construction sites, is growing dailiy. This work aims to identify based on a systematic review in the national literature, the utilization ratio of principles and tools of Lean Construction and contribution in the process of improvements in construction sites. Secondary objectives delimed on raising applying the principles of Lean Construction, evaluate the utilization ratio of the principles and tools and their contribution in the improvements process on construction sites and identify the scientific production related to Lean Construction. From the question of how the issue is being conducted in the literature and what is the relationship between the use of principles and tools of Lean Construction and its contribution in the process of improvements in construction sites, work possible answer them especially in a qualification of publications on the subject in national surveys. The conslusion of the research brings results as a computational tools BIM (Building Information Modelling) was the most studied tools between the articles in the last five years, 80% of authors did not mention the size of the company being P (small), M (medium) and L (large), there was a breathrough in publications on Lean Construction between the years 2011-2014, scientific approach, 80% of the articles relate to the practical application and 20% of theoretical application, focused highest number of publications that use principles: to introduce continuous improvements in processes and increase transparency of the process with 27% of the publications. The concept of the principles of Lean Construction verus the tool used being little explored in the scientific research, thus justifying proceed with discussion on the subject. Read the time referring to the main national publications, generating some volume of production in the area. Another example is the difficulty the academic...